CONTEMPORARY ENVIRONMENTAL HEALTH LAW PARADIGM: COMPREHENSIVE ANALYSIS OF LITERATURE REVIEW ON POLLUTION REGULATION FRAMEWORK, HAZARDOUS WASTE CONTROL, AND OCCUPATIONAL SAFETY STANDARDS IN THE HEALTH SECTOR FOR THE PREVENTION OF EPIDEMIOLOGICAL AND ECOLOGICAL RISKS - Gunawan Widjaja (Adisam Publisher, 2026)
This article presents a comprehensive analysis of the literature review on the contemporary environmental health law paradigm in Indonesia, focusing on the regulatory framework for pollution (Law No. 32/2009, Government Regulation No. 41/1999), the control of hazardous and toxic waste (Government Regulation No. 22/2021, Minister of Environment Regulation No. 6/2021), and occupational safety and health standards in the health sector (Minister of Health Regulation No. 66/2016, Ministry of Health Regulation No. 52/2018, Ministry of Manpower Regulation No. 5/2018), in order to prevent epidemiological risks such as nosocomial infections, antimicrobial resistance, and vector-borne outbreaks, as well as ecological risks in the form of water eutrophication, toxin bioaccumulation, and biodiversity degradation due to medical waste and emissions from health facilities. The normative juridical approach reveals the evolution of the paradigm from reactive anthropocentricity to proactive ecocentricity based on the polluter pays principle, the precautionary approach, and the OHS management system (ISO 45001). However, this is hampered by regional disparities, high processing costs (Rp10-15 million/tonne), as well as weak inter-agency supervision, which has resulted in only 60-70% of hospitals complying with hazardous waste quotas and 40% of workplace accidents occurring due to unsafe waste handling.ejournal. Reform recommendations include amending derivative regulations with AI-GIS monitoring, subsidising zero-waste technologies such as plasma pyrolysis, mandating a national P2K3RS committee, e-learning training, and harmonising ASEAN-PPP for synergistic dual risk prevention for a sustainable health ecosystem in line with SDGs 3, 6, 11, and 12.